DEVELOPMENT OF RIG HANGING HYDRO TURBINE BASED ON WASTE WATER DISCHARGE AT CHALLAWA INDUSTRIAL AREA OF KANO STATE (FUDMA JOURNAL OF SCIENCES, 2021)
Design of hydroelectricity system is employed here in an effort to produce electric energy using an exhaust waste water of steam power plant. The major concern in this work is how the system is designed, selection of site and resources. The system after designed and fabricated was mounted at waste water outlet for proof run for about three months period. The result obtained exhibit the overall design is feasible for the sensitive site application
Keywords: Hydro; micro hydro; renewable energy; waste water